Turnover of Technical-Administrative Education staff in Federal Higher Education Institutions: a state-of-the-art synthesis - Moura, Thaiani Candotte Mendonça de; Pozo, Osmar Vicente Chevez (Brazilian Journal of Production Engineering, 2026)
The turnover of Technical-Administrative Education (TAE) staff in Federal Educational Institutions (IFE) affects service continuity, talent retention, and the preservation of organizational knowledge. This study aimed to analyze recent research, identifying causes and assessing the impacts of the phenomenon. To achieve this, a bibliographic and documentary review of articles and dissertations published between 2015 and 2024 was conducted, synthesizing objectives, methods, findings, and limitations. Among the most frequent causes are dissatisfaction with salary and career plans, work overload, poor infrastructure, lack of recognition, and ineffective personnel management policies. Personal factors, such as seeking family proximity and better external opportunities, also influence resignations. The impacts include loss of institutional knowledge, increased workload for remaining staff, and a decline in administrative efficiency. Methodological and scope limitations reduce the generalizability of the results. It is concluded that broader and more integrated research is needed to support policies and strategies aimed at valuing, retaining, and developing TAE staff, thereby strengthening the career and the quality of services provided.